The Function of Language in Advertisements that Promote Fair Skin as a Beauty Standard - Simbolon, Lilis Veronika; Manik, Sondang; Sihite, Jubil Ezer (Kajian Linguistik dan Sastra, 2026)
This study examines the role of language in beauty advertisements that promote fair skin as a beauty standard. It aims to identify the language functions used and to explain how these functions contribute to the construction of fair skin as an ideal of beauty. The problem of this study focuses on how language is used to influence and shape audience perceptions in advertising discourse. This research employs a descriptive qualitative method. The data consist of 20 beauty advertisements collected from TikTok and YouTube, focusing on verbal elements such as slogans and persuasive expressions. The analysis is based on Roman Jakobson’s theory of language functions. The findings show that the conative function is the most dominant, followed by poetic and emotive functions. Overall, the study reveals that language in beauty advertisements plays a significant role in constructing and reinforcing fair skin as a beauty standard. Abstrak Penelitian ini mengkaji peran bahasa dalam iklan kecantikan yang mempromosikan kulit putih sebagai standar kecantikan. Penelitian ini bertujuan untuk mengidentifikasi fungsi-fungsi bahasa yang digunakan serta menjelaskan bagaimana fungsi-fungsi tersebut berkontribusi dalam pembentukan kulit putih sebagai ideal kecantikan. Permasalahan dalam penelitian ini berfokus pada bagaimana bahasa digunakan untuk memengaruhi dan membentuk persepsi audiens dalam wacana periklanan. Penelitian ini menggunakan metode deskriptif kualitatif. Data penelitian terdiri dari 20 iklan kecantikan yang dikumpulkan dari TikTok dan YouTube, dengan fokus pada unsur verbal seperti slogan dan ungkapan persuasif. Analisis didasarkan pada teori fungsi bahasa Roman Jakobson. Hasil penelitian menunjukkan bahwa fungsi konatif merupakan yang paling dominan, diikuti oleh fungsi puitik dan emotif. Secara keseluruhan, penelitian ini mengungkapkan bahwa bahasa dalam iklan kecantikan memainkan peran penting dalam membangun dan memperkuat kulit putih sebagai standar kecantikan.